If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = prt * t Multiply prt * t 1 = prt2 Solving 1 = prt2 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1prt2' to each side of the equation. 1 + -1prt2 = prt2 + -1prt2 Combine like terms: prt2 + -1prt2 = 0 1 + -1prt2 = 0 Add '-1' to each side of the equation. 1 + -1 + -1prt2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1prt2 = 0 + -1 -1prt2 = 0 + -1 Combine like terms: 0 + -1 = -1 -1prt2 = -1 Divide each side by '-1rt2'. p = r-1t-2 Simplifying p = r-1t-2
| [-28]-7= | | 144x^2-169=0 | | -8+2(4c+8)=8c+8 | | X+1=1+x | | 50=16w+14w | | -30+115= | | 6t-6+9t=69 | | 26=(2x-6)+(2x-6)+(x+3)+(x+3) | | 4.2q-1.2-5.5q=2.3q-3.9 | | 6x-3+5=6x+6 | | 25/50=x/100 | | 7y-13y+7= | | (x^2+4)=(8x-11) | | 4(1-7p)+4p=4-p | | 4.29-1.2-5.5=2.3-3.9 | | z/8-3=16 | | -2x=.75 | | 4(3x-5)= | | 20x-10+9=16x+14 | | 0=3x^2+4x-224 | | x=2(180-x) | | [8a+5(3-a)]-17= | | 5i-1=14(i) | | 2(6.4-0.5n)= | | 22-5x=(-28) | | 0.3(6+y)-0.3y=1.8 | | (a-b)+(3a+2b)= | | 18x+22=-14 | | q/9=32 | | x+15=-4x+4 | | 44=-52x | | 24=(x+4)+10(x-1)+4x |